Statistical steganalysis of four photo themes before embedding - Jabbar, Alaa A. (2013)
In order to analyze how the correlativity behavioral pattern would change after data embedding, it needs to conduct a statistical analyze on average, maximum, minimum, and standard deviation of each group of photo before embedding. This paper proposes and elaborates the details of a new steganalysis method and then presents the results and characteristics of the four photo themes. The behavioral patterns of the four photo themes before secret data embedding are extracted from pixel correlativity analysis (AND-analysis) and color channel correlativity analysis (OR-analysis) results of the photo samples in dataset. The extracted behavioral patterns can be used by researchers and steganalysts in examining photos.